Constitutional adjudication common themes and challenges - Grabenwarter, Christoph; Hering, Laura; Huber, Peter M; Bogdandy, Armin von 1960-; Krenn, Christoph 1986- (Max Planck Handbooks in European Public Law, 2023)
The fourth volume of the Max Planck Handbooks in European Public Law series compares European constitutional jurisdiction in the perspective of the European legal space. It examines the structures of the organization, the appointment of judges, the procedures and the methods of argumentation and interpretation, their impact on state and society, their legitimacy or their role in the division of powers, and thus completes the picture following the country reports in Volume III. This comparative perspective is supplemented by an examination that illustrates the relationship to the ECJ, the ECtHR and the Venice Commission as well as their (constitutional) function. Finally, the volume is devoted to the challenges currently facing constitutional jurisdiction in the European Legal Space. The historical, political, and theoretical foundations as well as the basic doctrinal features of constitutional jurisdiction are presented in such a way that the discussion about its role and further development in this legal space is sustainably stimulated"--